Elite archers' fitness rates in competitive adaptation process - Tarasova, L. V.; Zubarev, Y. N. (Theory and Practice of Physical Culture, 2017)
Abstract Modern developmental trends in archery are dictated by the growing numbers of top-ranking events the world over and the growing competition for leadership in the sport with the naturally growing role of the competitive adaptation mechanisms in elite sport and the need for studies of these mechanisms. Tests to rate the elite archers` physical fitness variations in the course of their adaptation to competitive environments have confirmed the need for special efforts to improve their physical fitness.